Development of transprofessional competitions as a new task for methods of foreign language teaching - Natalia A. Gridneva; Ksenia S. Oparina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the problem of transprofessional competences development by teaching foreign language in the professional education system. Its urgency is determined by considerably growing demand for specialists, which have not only well highly-specified competences, but also capacity for multidimensional activities and for successful work in an interdisciplinary team. Furthermore, the level of the study of the problem under consideration is theoretically and practically insufficient. Transprofessional competences are regarded as competences providing the ability of an employee to work beyond his or her obtained profession, to apply technologies of other professional spheres, to master new competences and find non-standard solutions. The discipline “Foreign language”, as shown in the article, has a high potential for development of transprofessional competences. But according to the results of our pretesting this potential remains predominantly unrealized: the foreign language teaching process is mostly organized based on former, partially outdated ideas about probable professional needs of a modern engineer. In the article we set a goal to elaborate methodological procedures for improvement of effectiveness of teacher’s work for that matter. We report on the most vital theoretical and practical aspects of our further vocational training course program, which we prepared for foreign language teachers to help them to choose more appropriate learning content and technologies and to perfect their skills needed for the most effective application of them.